Bisphosphonate prodrugs utilizing endogenous carriers - Giammei, Carolina (2016)
Targeting of therapeutic agents to a specific site, as well as controlling the rate and time of release, has been intensively investigated and established over the last decades. These studies concerning drug delivery systems led to the formulation of several products that can improve the diffusion across the barriers after drug administration. For this purpose, the development of strategies of novel drug delivery systems for bisphosphonates had taken hold to improve both the bioavailability and safety. Firstly, they have been used for over a century in the branch of industry and later, in the 1960s, in medicine. Bisphosphonates are synthetic compound analogs to the naturally occurring pyrophosphates. They are characterized by two phosphate groups bound to the same carbon atom, a ‘P-C-P’ moiety, and two functional groups R1 and R2. Mainly, bisphosphonates are effective inhibitors of bone resorption due to calcium disorders, such as osteoporosis, Paget’s disease, hypercalcemia of malignancy, multiple myeloma, and bone metastasis. Generally, they can be classified into two groups according to their mechanism of action: non-nitrogen containing bisphosphonates and nitrogen containing bisphosphonates. However, the therapeutic use of bisphosphonates is restricted by their poor oral bioavailability (less than 1%) due either to their hydrophilic properties and to the bulky and charged phosphonate groups. In order to overcome these issues and enhance the intestinal permeability of bisphosphonates, a prodrug design approach has been evaluated for these compounds. In the literature review of this thesis an overview of some of the available synthetic strategies, which involve the modification of the functional groups with a bioreversible promoiety according to the desired properties in the compound, is presented. The experimental part is aimed to conjugate bisphosphonates with bile acids in order to improve the oral bioavailability of the bisphosphonate. To optimize the yield, three different synthetic strategies were tested. In all syntheses sodium alendronate was used as the bisphosphonate and deoxycholic acid as the bile acid.